The Relationship Between Aspartate Aminotransferase To Alanine Aminotransferase Ratio And Metabolic Syndrome In Adolescents In Northeast China - Lin S (Dove Medical Press, 2019)
Shuang Lin,1,2 Lei Tang,1 Ranhua Jiang,3 Yu Chen,1 Sheng Yang,1 Ling Li,1 Ping Li1 1Department of Endocrinology, Shengjing Hospital of China Medical University, Shenyang, Liaoning Province, People’s Republic of China; 2Department of Cardiology, Zhongyi Northeast International Hospital, Shenyang, Liaoning Province, People’s Republic of China; 3Department of Endocrinology, Liaoyang Diabetes Hospital, Liaoyang, Liaoning Province, People’s Republic of ChinaCorrespondence: Ping LiDepartment of Endocrinology, Shengjing Hospital of China Medical University, No.39, Huaxiang Road, Tiexi District, Shenyang 110022, Liaoning Province, People’s Republic of ChinaTel +86 18940255673Email scizhong@163.comLing LiDepartment of Endocrinology, Shengjing Hospital of China Medical University, No.36, Sanhao Street, Heping District, Shenyang 110004, Liaoning Province, People’s Republic of ChinaTel +86 18940251181Fax +86 02425944460Email liling8864@hotmail.comAim: To investigate the relationship of the aspartate aminotransferase to alanine aminotransferase ratio (AST/ALT) and metabolic syndrome (MetS) in adolescents in northeast China.Methods: A stratified cluster random sample of 935 students 11–16 years of age in a city in the northeast of China were enrolled in 2010–2011. Participants were given a physical examination and a laboratory evaluation, and 93 participants were followed-up after 5 years.Results: AST/ALT was negatively correlated with waist circumference (WC), waist-to-hip ratio, body mass index (BMI), diastolic blood pressure, triglycerides, low-density lipoprotein, uric acid, fasting insulin, and insulin resistance. It was positively correlated with high-density lipoprotein. Multivariate logistic regression showed that the risk of MetS was 6.02 times greater in adolescents with the lowest, compared with the highest, AST/ALT. Central obesity was the MetS component most closely associated with low AST/ALT [odds ratio (OR) =5.13, 95% CI: 2.83, 9.28]. Five years later, baseline AST/ALT was negatively correlated with WC (r=−0.21, P=0.046), BMI (r=−0.29, P=0.005) and fasting plasma glucose (r=−0.25, P=0.017).Conclusion: In adolescents, AST/ALT was significantly associated with MetS and its components and predicted overweight/obesity in adulthood.Keywords: metabolic syndrome, aspartate aminotransferase, alanine aminotransferase, adolescents